Innovation of Early Talent Development of Primary Education Students Based on Total Quality Management - Badrus, Badrus; Rahman, Marita Lailia; Sulthon, Muhammad (Didaktika Religia, 2022)
The lack of creativity of parents and educational institutions in exploring children’s talents can have an impact on the reduced innovation of student talent development. On a broader scale, innovation of underdeveloped student talent can result in limited contributions to important work that can hinder the progress of various fields in the future. This research uses a qualitative descriptive method, with the method of extracting observation data, interviews, and documentation. While data analysis uses Miles and Hubberman’s theory, namely, data reduction, data display, and conclusion drawing. The results showed that the teacher’s strategy in detecting students’ talents was carried out through four stages. First, internal exploration of students by giving freedom to choose the talents to be developed. Second, treatment of talent tests. Third, confirmation with parents. And Fourth, final determination of talents. Talent development strategy is carried out through two channels. First, internal madrasah coaching pathway. And second, external coaching through course institutions and training in Madrasah Ibtidaiyah environment. To ensure the continuous growth of student talent, Madrasah conducts cooperation with parents, course institutions, and training with a mutually agreed memorandum of understanding (MoU). This form of cooperation is a new talent development management strategy that can provide progressive results for the development of student talent.